Effect of nano-SiO₂ and lime on characteristics and mechanical properties of coastal clay - Wentao Shang; Zhong Liu; Yuqin Gao (Functional Materials, 2019)
In this study, the effect of nano-SiO₂ and lime on the characteristics and mechanical properties of coastal clay were investigated. The California bearing ratio (CBR) test and hydraulic conductivity tests were performed to investigate the improved coastal clay strength and hydraulic parameters. The clay specimens were prepared in 5 groups: unmixed, mixed with 3 % lime, 5 % lime, 3 % lime + 1.5 % nano-SiO₂ and 5 % lime + 3 % nano-SiO₂. The results show that the cementation of nano-SiO2 and lime leads to larger CBR values and lower permeability of the coastal clay. Scanning electron microscopy reveals that nano-SiO₂ particles fill in the interspace between lime particles or gel pores, with the diameters of capillary pores and micro-pores reduced.